2015
DOI: 10.1007/s10965-015-0780-9
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric relaxation and ferromagnetic resonance in magnetoelectric (Polyvinylidene-fluoride)/ferrite composites

Abstract: In this work the dielectric properties and ferromagnetic resonance of Polyvinylidene-fluoride embedded with 10 wt. % of NiFe 2 O 4 or Ni 0.5 Zn 0.5 Fe 2 O 4 nanoparticles are presented. The mechanisms of the dielectric relaxation in these two composites do not differ from each other. For more precise characterization of the dielectric relaxation, a two dimensional distribution of relaxation times was calculated from the temperature dependencies of the complex dielectric permittivity. The results obtained from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 38 publications
2
9
0
Order By: Relevance
“…Such its behavior generally means that the dipolar system has a broad distribution of relaxation time [29]. In our composites this dispersion can be attributed to amorphous relaxation of PVDF, particularly to the freezing of dipolar motions since it is seen in pure PVDF as well as in PZT-PVDF and PZT-PVDF- ferrite composites that is in agreement with results observed earlier in literature [30][31][32]. The second dispersion region which appears above the room temperature is partially overlapped with the PVDF dispersion and gets stronger above 350 K. There is no clear definition about its origin and can be associated with the wide-angle oscillation of dipolar groups of PVDF [31] or with Maxwell-Wagner relaxation induced by chemical inhomogeneity thus forming space charge-rich regions between PZT and CF/NZF and PVDF matrix.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Such its behavior generally means that the dipolar system has a broad distribution of relaxation time [29]. In our composites this dispersion can be attributed to amorphous relaxation of PVDF, particularly to the freezing of dipolar motions since it is seen in pure PVDF as well as in PZT-PVDF and PZT-PVDF- ferrite composites that is in agreement with results observed earlier in literature [30][31][32]. The second dispersion region which appears above the room temperature is partially overlapped with the PVDF dispersion and gets stronger above 350 K. There is no clear definition about its origin and can be associated with the wide-angle oscillation of dipolar groups of PVDF [31] or with Maxwell-Wagner relaxation induced by chemical inhomogeneity thus forming space charge-rich regions between PZT and CF/NZF and PVDF matrix.…”
Section: Resultssupporting
confidence: 92%
“…These low-frequency relaxations of ε' appearing at low frequencies below 400 kHz in all samples can be referred to defects creating interface polarization owing to the charge accumulation at the boundary between different phases caused by different Maxwell-Wagner polarization mechanism and may be predominating in the total conduction of this family of materials. The relaxation dispersion starting to emerge above 400 kHz is obviously related to the glass transition relaxation of the PVDF matrix [31,32,35]. Figure 9 shows that pure PVDF film has dielectric constant around 10 in whole frequency range at room temperature.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Additionally, due to the chemical inertness, PVDF-based materials are suitable for applications in relatively harsh conditions [13].…”
Section: Introductionmentioning
confidence: 99%
“…frequency and temperature) because these properties determine the performance of ME materials in telecommunications, electronics, biomedicine and some other fields [13,17]. No previous studies can be found in the literature regarding the temperature dependences of those responses of CoFe 2 O 4 /P(VDF-TrFE) nanocomposites.…”
Section: Introductionmentioning
confidence: 99%